The Effect of Aerobic Exercises on Skill Behaviour of Autestic Children - Yusuf Burak Yamaner, Abdullah Demirli, Abdorreza Eghbal Moghanlou, Eda Gökçelik (Pakistan Journal of Medical & Health Sciences, 2022)
The main reason of this research was to find the effect of twelve weeks of Aerobic exercises on skill behaviors of autistic children. The present study was a quasi-experimental research which was conducted as a pre-test and post-test. Participants of the present study included 30 voluntarily children with autism symptoms (8-10 yrs old) of Bartin city. They were randomly divided in two groups of 15 experimental and control groups. Before completing the exercises, Gars questionnaire was completed by parents. The experimental group performed Aerobic exercises under the supervision of an instructor and a psychologist for three sessions of 45 minutes a week for 3 months. At the end, both experimental and control groups were measured and parents completed the Gars questionnaire once again. For analysis of data SPSS 22 software was used at p≥0.05. Analysis of variance in repeated measures test was taken to find data. The results showed that twelve weeks of Aerobic exercises has a significant effect on the coordination and agility of autistic children.